2021
DOI: 10.1111/jdv.17547
|View full text |Cite
|
Sign up to set email alerts
|

Small‐vessel vasculitis following Oxford‐AstraZeneca vaccination against SARS‐CoV‐2

Abstract: mask induced acne) in health care professionals of tertiary care hospitals of Lahore during COVID-19 Pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
“… 7 On the contrary, vasculitis was also reported after COVID‐19 vaccination. Several case reports were reported skin vasculitis following vector‐based vaccines including AZ 27 , 28 , 29 and Johnson Johnson. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Injection‐site skin reaction has been reported as a common adverse drug reaction; however, there has been only one report of vasculitis so far with the ChAdOx1 nCoV‐19 vaccine. 1 Herein, we present a case of new‐onset leukocytoclastic vasculitis following ChAdOx1 nCoV‐19 vaccination.…”
Section: Figurementioning
confidence: 98%